Twelfth Finance Commission View from Kerala - K P KANNAN, R MOHAN (Economic and Political Weekly June 5, 2004, 2004)
The focus of the paper is to review the Terms of Reference (TOR) of the Twelfth Finance Commission with special reference to Kerala. It also critically examines the emphasis on fiscal deficit reduction without paying attention to its quality and finds that this has led to the centre and the states resorting to a softer option of cutting productive capital and necessary maintenance and social sector expenditure. This is likely to have adverse consequences on equitable growth and to impede the process of relieving the economy of structural constraints on growth. The study suggests incorporating the concept of quality of fiscal discipline